2018
DOI: 10.1002/jso.25095
|View full text |Cite
|
Sign up to set email alerts
|

Adult soft tissue sarcoma and time to treatment initiation: An analysis of the National Cancer Database

Abstract: The median TTI in the United States for STS is 22 days. Increased TTI in STS are associated with tumor and treatment characteristics, socio-economic factors and hospital systems issues. Transitions in care between institutions are responsible for the greatest increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 51 publications
0
13
0
1
Order By: Relevance
“…In the current study, Figure 3 delineates those factors that were attributed to increased or decreased TTI in PBS. As has been previously noted with soft tissue sarcoma, the single largest factor associated with increased TTI is a transition in care [ 12 ].…”
Section: Discussionmentioning
confidence: 90%
“…In the current study, Figure 3 delineates those factors that were attributed to increased or decreased TTI in PBS. As has been previously noted with soft tissue sarcoma, the single largest factor associated with increased TTI is a transition in care [ 12 ].…”
Section: Discussionmentioning
confidence: 90%
“…Recent SEER-based studies have suggested that an association exists between insurance status and the presence of metastases at the diagnosis for certain soft tissue sarcoma subtypes [ 18 , 19 ]. Additionally, an NCDB study found that Medicare, Medicaid, or no insurance was correlated with increased time to treatment initiation, whereas median income > $63,000 was associated with shorter time to treatment initiation [ 20 ]. While the further analysis did not reveal these associations in our study cohort, there was an association between facility type and insurance status (P = 0.031).…”
Section: Discussionmentioning
confidence: 99%
“…166 Conversely, a review of the NCDB identified 41,529 patients with STS and found that increased timing to treatment was associated with socioeconomic factors and issues within hospital systems. 167 Another factor seen in clinical treatment patterns includes variation in the management of extremity STS, where a study described age as being a factor of treatment, with young adults more likely to receive chemotherapy and less likely to receive RT when compared to older groups. 168 In a retrospective database review, the impact of age showed an overall lower local recurrence rate in primary amputations of elderly patients (over 90 years) when compared to limb salvage.…”
Section: Clinical Treatment Patterns and Outcomesmentioning
confidence: 99%
“…A retrospective cohort study described the interplay of social and tumor characteristics in determining diagnostic intervals, finding that tumor characteristics, rather than social factors, determined longer diagnostic intervals among patients 166 . Conversely, a review of the NCDB identified 41,529 patients with STS and found that increased timing to treatment was associated with socioeconomic factors and issues within hospital systems 167 . Another factor seen in clinical treatment patterns includes variation in the management of extremity STS, where a study described age as being a factor of treatment, with young adults more likely to receive chemotherapy and less likely to receive RT when compared to older groups 168 .…”
Section: Disparities Of Care In Stsmentioning
confidence: 99%